Sleep-disordered breathing and risk of lung cancer: a meta-analysis longitudinal follow-up studies - Ma, Hongfu; Zhang, Xuefeng; Han, Jin; Li, Fenghuan (European journal of cancer prevention, 2022)
Consensus remains lack regarding whether sleep-disordered breathing (SDB) is an independent risk factor for lung cancer. We therefore conducted a meta-analysis to clarify the relationship of SDB and lung cancer. Longitudinal follow-up studies investigating the association between SDB and incidence of lung cancer were included by search of electronic databases including PubMed, Embase, and Cochrane's Library. A random-effects model was adopted to combine the results. Seven studies were included. Pooled results showed that presence of SDB was independently associated with higher incidence of lung cancer [adjusted risk ratio (RR): 1.28; 95% confidence interval (CI), 1.11-1.47; P < 0.001; I2 = 37%]. Sensitivity analysis limited to studies with adjustment of smoking showed consistent results (three studies, RR: 1.34; 95% CI, 1.22-1.48; P < 0.001; I2 = 8%). Subgroup analysis suggested that the association between SDB and higher risk of lung cancer was not significantly affected by study characteristics such as study design, source of population, sample size, evaluation methods for SDB, follow-up duration, methods for validation of lung cancer, or score of study quality (P values for subgroup difference all >0.05). No significant publication bias was observed (P for Egger's regression test = 0.258). These results suggested that SDB may be an independent risk factor of lung cancer in adult population. Intensive screening and prevention of lung cancer in subjects with SDB should be considered.